EVOLUTION OF ENVIRONMENTAL JURISPRUDENCE IN PAKISTAN: FROM STATUTORY FRAMEWORKS TO CLIMATE JUSTICE (Contemporary Journal of Social Science Review, 2026)
Pakistan’s environmental jurisprudence has evolved from colonial resource-centric regulation to a decentralized and rights-based climate governance framework. The Pakistan Environmental Protection Act (PEPA) 1997 established the foundational structure for environmental regulation through Environmental Impact Assessment (EIA), pollution control mechanisms, and environmental adjudication. However, the increasing frequency of climate-induced disasters and the constitutional devolution introduced through the 18th Amendment shifted environmental governance toward provincial autonomy and climate resilience. This paper critically examines the evolution of environmental law in Pakistan from the colonial period to 2026, with particular emphasis on the transition from PEPA 1997 to the Climate Change Act 2017. It analyzes the emergence of environmental constitutionalism through judicial activism, especially under Article 9 of the Constitution, where the judiciary expanded the “Right to Life” to include environmental protection, sustainable development, and climate justice. Landmark cases such as Shela Zia v. WAPDA and Leghari v. Federation of Pakistan are examined as pivotal developments in climate jurisprudence. The study further evaluates provincial environmental governance, international environmental commitments, and implementation challenges related to institutional fragmentation, weak enforcement, and climate vulnerability. The paper argues that Pakistan’s environmental legal regime has transitioned from conventional pollution-control governance toward a broader framework of environmental constitutionalism and climate justice grounded in sustainability, intergenerational equity, and ecological resilience.